Morphological and Syntactical Error Analysis on The Students’ Descriptive Composition of Private Vocational High School - nia liska saputri (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
The aim of this research is to find out morphological and syntactical errors made by the students in their composition, the frequency of errors and the dominant type of error, the sources of error, and find a remedial teaching. The method that was used in this research is descriptive method, a method which seeks to provide the depicition or description of a case. This research conducted on the second semester of 2016/2017 in SMK Kharismawita 2 Jakarta. Meanwhile, the sample of this research is 30 students of XI APh class of SMK Kharismawita 2. In this case, the researchers use purposive sampling in choosing the sample and the method of this research is qualitative research.In this research the researchers are going to find some morphological errors made by the students, these errors can be classified into 9 categories of morphological errors. These are categories, number, percentage of morphological errors made by the students : adverbs, adjectives, indefinite demonstratives, adjectives, nouns, plurals, possesive adjectives, past formations, singulars and to infinitives.Meanwhile, in this research, the researchers are going to find some syntactical errors made by the students. These categories are categorized based on surface strategy taxonomy. These are the categories, the numbers and the percentage : omission, addition, misformation, and misordering.